2018
DOI: 10.1515/hf-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic feasibility of bioethanol production via biorefinery of olive tree prunings (OTP): optimization of the pretreatment stage

Abstract: The aim of this work was to evaluate the economic feasibility of the bioethanol production (BEP) based on olive tree pruning (OTP) as a biomass feedstock with optimization of the dilute acid pretreatment in focus. For this, the BEP was simulated taking into account the influence of the operating conditions of the pretreatment stage. Then, the techno-economic results were analyzed by means of the response surface methodology (RSM). The results show that lowest price of BE was 1.94 USD l−1 with a yield of 174.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…The main residues and by-products produced in this industry are olive tree pruning (OTP), derived from the pruning operation in olive tree crop; extracted dry olive pomace (EOP), produced in olive oil pomace extraction industries; and olive leaves (OL) and stones (OS), produced at different steps of the olive oil extraction process in olive mills [4]. Several studies have already demonstrated the considerable potential of using OTP as a feedstock in a multi-product biorefinery, with focus on bioethanol as the main product among other valuable compounds such as xylitol and antioxidants [5][6][7]. Furthermore, EOP and OL have also been evaluated as valuable sources of antioxidants, biofuels and bioenergy in a process strategy that would be applied as a multi-feedstock biorefinery built around the olive oil sector [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The main residues and by-products produced in this industry are olive tree pruning (OTP), derived from the pruning operation in olive tree crop; extracted dry olive pomace (EOP), produced in olive oil pomace extraction industries; and olive leaves (OL) and stones (OS), produced at different steps of the olive oil extraction process in olive mills [4]. Several studies have already demonstrated the considerable potential of using OTP as a feedstock in a multi-product biorefinery, with focus on bioethanol as the main product among other valuable compounds such as xylitol and antioxidants [5][6][7]. Furthermore, EOP and OL have also been evaluated as valuable sources of antioxidants, biofuels and bioenergy in a process strategy that would be applied as a multi-feedstock biorefinery built around the olive oil sector [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This means that there is a large remaining fraction that can be applied for other purposes. Instead of a stand-alone process, the process based on the principles of biorefinery would increase the profitability [12]. This means that olive leafy byproducts can be complementarily used as feedstock for the production of second generation bioethanol from their sugar fraction [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Bioethanol production process economic assessment usually includes the estimation of yields, financial considerations, and costs related to the investment and operating costs. To determine the efficiency of the pre-treatment process, the bioethanol yield from the hybrid biomass (cassava peels and yam peels biomass) for the acid-based and alkali-based pre-treatments were evaluated using the model used by Solarte-Toro et al 28 . The assessment also included obtaining the utility costs, which comprise the cooling water, steam, fuel, and electricity required for pre-treatment, fermentation, and distillation of the fermented hydrolysates, cost of raw materials and transportation, labour costs, operating charges, Fermentation and distillation equipment Costs, administrative costs, cost of enzymes and depreciation.…”
Section: Methodsmentioning
confidence: 99%